2014
DOI: 10.1248/bpb.b14-00000
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes, but Not Neurons, Exhibit Constitutive Activation of P2X7 Receptors in Mouse Acute Cortical Slices under Non-stimulated Resting Conditions

Abstract: We previously demonstrated that the P2X7 receptor (P2X7R), a purinergic receptor, expressed by mouse cultured cortical astrocytes is constitutively activated without any exogenous stimulus, differing from the case of neurons. It is well known that astrocytic morphology differs between in vitro and in vivo situations, implying different functionalities. Brain acute slices are widely accepted as an in vitro experimental system that reflects in vivo cell conditions better than in vitro cell culture ones. We exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Interestingly, a number of articles reported the presence of P2X7R in astrocytes ( Kamatsuka et al, 2014 ; Gao et al, 2017 ; Khan et al, 2019 ), including a work on iPSC-derived cells ( Kesavan et al, 2021 ). Some of these reports suggest that the astrocytic P2X7R indirectly regulates neuronal activity ( Khan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a number of articles reported the presence of P2X7R in astrocytes ( Kamatsuka et al, 2014 ; Gao et al, 2017 ; Khan et al, 2019 ), including a work on iPSC-derived cells ( Kesavan et al, 2021 ). Some of these reports suggest that the astrocytic P2X7R indirectly regulates neuronal activity ( Khan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gap junctional networks of astrocytes are more common and generally more extensive, whereas little evidence is available for gap junctions among SCN neurons (Welsh and Reppert, 1996 ; Colwell, 2000 ). The P2X7R protein is also well-documented to be expressed on astrocytes (Narcisse et al, 2005 ; Sperlágh et al, 2006 ; Hamilton et al, 2008 ; Kamatsuka et al, 2014 ; Zhao et al, 2016 ), whereas its expression in neurons is still questionable (Illes et al, 2017 ). Our present study also shows the expression of the P2X7R protein in SCN astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We found transient increases in extracellular ATP within restricted subcellular regions of astrocytes (Fig. 2C-E; area: 124.16 (37.28, 381.6) µm 2 ; full width at half maximum (FWHM): 6 (5,14) sec; peak ∆F/F0: 51.4% (41.7%, 65.8%); median (interquartile ranges [IQRs]) in 12 events from 30 cells in 6 mice). Such transient and localized ATP events were also found in acute brain slices without stimulation (Fig.…”
Section: Cortical Astrocytes Spontaneously and Locally Release Atpmentioning
confidence: 92%
“…Not only is ATP released from astrocytes in response to neuronal inputs, but Koizumi et al found tetrodotoxin-insensitive ATP release in neuron-glia co-culture (12). Tonic ATP release was reported in brain slice preparations (13)(14)(15), but it was unclear whether astrocytes release ATP spontaneously or in response to the basal neuronal firing. Investigating basal ATP release activity will provide a further perspective on how astrocytes are involved in the neuron network function.…”
Section: Introductionmentioning
confidence: 99%